EArticle RETRACTED due to manipulation by the authors Physical fitness, motor ability, motivation and physical literacy knowledge of primary school students in Pontianak city, Indonesia - Andika Triansyah; Fitriana Puspa Hidasari; Witri Susanto; Doni Pranata; Amran Amran; Kukuh Wahyudin Pratama (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to analyze the level of physical fitness, motor skills, level of motivation and physical literacy knowledge of elementary school students in Pontianak City. The population in this study were elementary school students in the city of Pontianak. This type of research is purposive sampling, so the sample is 273 people. After the data is obtained, the research data analysis technique uses frequency tabulation. The results of this research show: The level of physical fitness among elementary school students in the city of Pontianak who used the pacer test using the latest adaptation of the Indonesian student fitness test. The results showed that the level of physical fitness among elementary school students in the city of Pontianak was 62 students (43.35%) were declared to have a good fitness level, 47 female students (36.15%) were declared to have a good fitness level. The level of motor skills in elementary school students in the city of Pontianak, namely 62 students (43.35%) were declared to have a good level of motor skills, while the research results for the female sample were 54 female students (41.53%) were declared to have a good level of motor skills. Moderate motor skills. Regarding motivation, the results were motivation in elementary school students in the city of Pontianak, namely 71 students (49.65%) were declared to have achieved levels of motivation, while the research results for the female sample were 56 female students (43.07%) stated have a level of progressing motivation. Regarding physical literacy knowledge, the physical literacy abilities of elementary school students in Pontianak City, namely 71 students (49.65%) were declared to have achieved levels of physical literacy abilities, while the research results for the female sample were 49 female students (37 . 69%) were declared to have a level of achievement motivation.